Design and testing of a soil-dividing device for a pineapple strip-tillage furrower - Haitian Sun; Wei Zhang; Hongxuan Wang; Hailiang Li; Peng Sun; Huafen Zou; Chun Wang; Meigu Lu; Zhong Xue (PLoS ONE, 2026)
To address issues such as high soil backfilling rates and difficulty in maintaining the trench shape during the operation of pineapple strip-rotary cultivators, we designed a V-shaped soil-dividing device. Structural modelling was performed using SolidWorks 2022 by establishing force analysis equations for the soil-dividing device and soil motion trajectory equations. A dynamic simulation model based on the discrete element method was constructed using the EDEM software to determine the structural parameters of the soil-dividing device. Stress analysis conducted using the ANSYS software verified that the structural strength of the soil-dividing device met the application requirements. To optimize operational parameters further, a four-factor, five-level orthogonal rotational combination field trial was designed using the central composite response surface method in Design-Expert 12. The installation distance, V-angle, blade roller speed, and forward speed were defined as the experimental factors, with the soil backfilling rate as the evaluation indicator. We analyzed the effects of various factor interactions on the soil backfilling rate. The experimental results indicated that the minimum soil backfilling rate of 38.12%, which is satisfactory for pineapple planting trenching requirements, was achieved at a V-angle of 30°, forward speed of 3.7 km/h, blade roller speed of 290 r/min, and installation distance of 125 mm. This study has significant implications for advancing the mechanization of pineapple cultivation.